Gambaran Pengetahuan Penderita Hipertensi Tentang Efektifitas Terapi Bekam Sebagai Terapi Komplementer - Merta Jaya, I Komang Alit; Arwidiana, Dewa Putu; Candrawati, Sang Ayu Ketut (Pustaka Galeri Mandiri, 2025)
Patients’ knowledge regarding the benefits of cupping therapy plays an important role in determining their decisions in choosing treatment. Low levels of knowledge may lead to inappropriate hypertension management behaviors, such as non-adherence to treatment and limited use of supportive therapies, resulting in uncontrolled blood pressure and an increased risk of complications. Hypertension is a chronic disease that requires long-term management, including the use of complementary therapies as an adjunct to medical treatment. Cupping therapy is one of the options believed to help reduce blood pressure. This study aimed to describe the level of knowledge of hypertensive patients regarding the effectiveness of cupping therapy as a complementary treatment at the Dawan Usadha Independent Nursing Practice. The study employed a quantitative descriptive design with a cross-sectional approach, involving 71 respondents selected through purposive sampling. The instrument used was a Guttman-scale knowledge questionnaire that had been tested for validity and reliability. The results showed that 50.7% of respondents had good knowledge, 40.8% had sufficient knowledge, and 8.5% had poor knowledge. The researchers assessed that respondents’ good level of knowledge was influenced by educational background, access to information, and personal experience. Overall, hypertensive patients demonstrated good knowledge regarding the effectiveness of cupping therapy